2016
DOI: 10.1093/nar/gkw725
|View full text |Cite
|
Sign up to set email alerts
|

Evoking picomolar binding in RNA by a single phosphorodithioate linkage

Abstract: RNA aptamers are synthetic oligonucleotide-based affinity molecules that utilize unique three-dimensional structures for their affinity and specificity to a target such as a protein. They hold the promise of numerous advantages over biologically produced antibodies; however, the binding affinity and specificity of RNA aptamers are often insufficient for successful implementation in diagnostic assays or as therapeutic agents. Strong binding affinity is important to improve the downstream applications. We report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
116
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 70 publications
(75 reference statements)
2
116
0
Order By: Relevance
“…With a salt-gradient elution mode on tertiary or quaternary ammonium-derivatized polymeric adsorbent or porous silica, the oligonucleotides could be separated by the ion-exchange chromatography method. Several kinds of advance structure, such as secondary, tertiary, dimers, or aggregates may exist in oligonucleotides, so denaturing conditions are required for these types of structures which could be achieved by adding organic solvents such ethanol or acetonitrile, using high-pH buffers or high temperature (55 to 65 °C depending on the column) [11,14,26]. …”
Section: Separation and Purification Of Oligonucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…With a salt-gradient elution mode on tertiary or quaternary ammonium-derivatized polymeric adsorbent or porous silica, the oligonucleotides could be separated by the ion-exchange chromatography method. Several kinds of advance structure, such as secondary, tertiary, dimers, or aggregates may exist in oligonucleotides, so denaturing conditions are required for these types of structures which could be achieved by adding organic solvents such ethanol or acetonitrile, using high-pH buffers or high temperature (55 to 65 °C depending on the column) [11,14,26]. …”
Section: Separation and Purification Of Oligonucleotidesmentioning
confidence: 99%
“…Additionally, some modifications have been introduced, such as phosphorothioate linkages, incorporating modified nucleosides as 2′-OMe, 2′-OMOE, or 2′-F in the sequence, and attaching polyethylene glycol at the terminus to the structures of oligonucleotides in order to increase stability and bioavailability. However, these modifications also enhanced the challenges for analysis and purification [10,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…23 Recent studies have shown that combined 2′-OMe-PS2 or 2′-F-PS2 substitution experiments with in vitro selected RNA aptamers 24, 25 led to either a reduction or increase in binding affinity. 26 A destabilizing effect by 2′-modification could be due to altered sterics (2′-OMe vs. 2′-OH), loss of H-bonding (2′-OMe vs. 2′-OH), or arise as a consequence of modifying a residue that adopts a C2′- endo pucker, i.e. shifting the conformational equilibrium to C3′- endo compared to the native ribose (as seen with the 2′-F analog).…”
mentioning
confidence: 99%
“…Evaluation consisted of using a serial dilution of MS2 protein screened against individual hairpin RNA variants that were immobilized onto streptavidin coated BLI sensors. 26, 29 Binding and dissociation rates of native hairpin RNA were determined in parallel to the variants. Supplementary Figure 1 (SF-1) shows the characterization of native RNA and all of its PS2 modified variants.…”
mentioning
confidence: 99%
See 1 more Smart Citation